THE USE OF PHONETIC RHYTHMICITY AS A SCIENTIFIC-METHODICAL PROBLEM IN THE DEVELOPMENT OF THE SPEECH OF SPECIAL NEEDS ELEMENTARY SCHOOL STUDENTS - O.S, Ishmatova (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2023)
Annatation: this article analyzes the scientific and methodological aspects of the use of phonetic rhythmics in the development of speech of primary students with special needs.